Magnetically Actuated Reconfigurable Metamaterials as Conformal Electromagnetic Filters. (21st September 2022) - Wu, Shuai; Eichenberger, Jack; Dai, Jize; Chang, Yilong; Ghalichechian, Nima; Zhao, Ruike Renee
Abstract : Electromagnetic Filters In article number 2200106, Renee Zhao and co‐workers report reconfigurable electromagnetic metamaterials based on magnetically responsive lattices. The magnetic actuation enables fast and programmable structural reconfigurations between flat deployed/folded and curved deployed/folded states for both conformal and freestanding metamaterials. The integrated customizable subwavelength patterns effectively switch the metamaterial between accepting and rejecting incident electromagnetic waves upon structural reconfiguration.